2010
DOI: 10.1002/chem.201001481
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic In Situ Investigation of the Morphogenesis of Grains during Pressure‐Induced Phase Transitions: Molecular Dynamics Simulations of the B1–B2 Transformation of RbCl

Abstract: The mechanistic details of the pressure-induced B1-B2 phase transition of rubidium chloride are investigated in a series of transition path sampling molecular dynamics simulations. The B2→B1 transformation proceeds by nucleation and growth involving several, initially separated, nucleation centers. We show how independent and partially correlated nucleation events can function within a global mechanism and explore the evolution of phase domains during the transition. From this, the mechanisms of grain boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…In contrast to this, first order transitions occur via nucleation and phase growth, and molecular organization occurring at the reactive interface for these transitions is unlikely to follow the structural changes proposed by Buerger-type analysis (see below in Section 5). This is also reflected by the final state found after a first order phase transition, as multiple nucleation events generally yield polycrystalline or domain structures with single crystal to single crystal transitions being exceptions and typically limited to small or nanocrystals [28,60].…”
Section: Molecular Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to this, first order transitions occur via nucleation and phase growth, and molecular organization occurring at the reactive interface for these transitions is unlikely to follow the structural changes proposed by Buerger-type analysis (see below in Section 5). This is also reflected by the final state found after a first order phase transition, as multiple nucleation events generally yield polycrystalline or domain structures with single crystal to single crystal transitions being exceptions and typically limited to small or nanocrystals [28,60].…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…In other terms, such reconstructive transformations provide comparably low strain within the phase domains at the cost of relatively high interface energy. For instance, reconstructive transitions were observed for the pressure-induced B1B2 transformation in alkali halides[60,133] (Figure 15). For these compounds transition-path sampling molecular dynamics simulations revealed that nucleation starts with the displacement of a single ion, followed by shifting of an entire column.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, within the last decade, TPS simulations have revolutionized the investigation of solid-solid transformations by offering unbiased in situ investigations of phase nucleation and growth at the atomic level of detail. [22][23][24][25][26][27] Earlier, we reported molecular dynamics simulations of the b to a phase transformation in bulk crystals of DL-norleucine (2-aminohexanoic acid, C 6 H 13 NO 2 ) at a series of temperatures up to 390 K. 28,29 Both the a and b forms of DL-norleucine contain a 1 : 1 ratio of the R and S enantiomers in their respective lattices (Fig. 1) and display a similar molecular packing in the form of bilayers connected by tight hydrogen bonding between the -COO-and -NH 3 + groups.…”
mentioning
confidence: 99%